2018
DOI: 10.15381/rivep.v29i2.14481
|View full text |Cite
|
Sign up to set email alerts
|

Parámetros productivos y económicos de gallinas ponedoras ISA Brown en segundo ciclo de producción suplementadas con aminoácidos no esenciales

Abstract: El estudio buscó evaluar parámetros productivos y económicos en gallinas ponedoras de segundo ciclo Isa Brown suplementadas con glutamina + ácido glutámico (Aminogut®). Se evaluaron cuatro niveles del producto comercial (0, 0.8, 1.6 y 2.4%) en dietas para gallinas ponedoras de segundo ciclo durante trece semanas de producción (45-119 días). Se colectaron datos de desempeño productivo y se evaluaron parámetros económicos. La suplementación de la ración con Aminogut® al 1.6% mejoró el número de huevos por ave al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
2
4
5
Order By: Relevance
“…For all the treatments, FCR (in kilograms of feed per dozen eggs) was similar to that reported by Morales et al (2018b) (1.65-1.82 kg feed/dozen eggs) for the SCLH of the Isa Brown line for 17 weeks of production and Sgavioli et al (2013) (1.77 kg feed/dozen eggs) for 71-week-old Isa Brown hens during 112 days of postmolt production. Met+Cys allows an increase in crude protein in albumen and yolk and improves EP, FCR, egg size, and EW (Oliveira Filho, 2019).…”
Section: Production Parameterssupporting
confidence: 82%
See 4 more Smart Citations
“…For all the treatments, FCR (in kilograms of feed per dozen eggs) was similar to that reported by Morales et al (2018b) (1.65-1.82 kg feed/dozen eggs) for the SCLH of the Isa Brown line for 17 weeks of production and Sgavioli et al (2013) (1.77 kg feed/dozen eggs) for 71-week-old Isa Brown hens during 112 days of postmolt production. Met+Cys allows an increase in crude protein in albumen and yolk and improves EP, FCR, egg size, and EW (Oliveira Filho, 2019).…”
Section: Production Parameterssupporting
confidence: 82%
“…The highest cumulative number of hen-housed eggs found in our work was 105.1, with an average of 5.25 eggs per week (diet 13). This result is higher than that reported by Morales et al (2018b), who found between 4.52 and 5.01 cumulative hen-housed eggs from ISA Brown SCLH of 83-100 weeks old.…”
Section: Production Parameterscontrasting
confidence: 72%
See 3 more Smart Citations